Nutritional evaluation of mixed wheat–faba bean pasta in growing rats: impact of protein source and drying temperature on protein digestibility and retention. Issue 5 (30th January 2019) - Laleg, Karima; Salles, Jérôme; Berry, Alexandre; Giraudet, Christophe; Patrac, Véronique; Guillet, Christelle; Denis, Philippe; Tessier, Frédéric J.; Guilbaud, Axel; Howsam, Michael; Boirie, Yves; Micard, Valérie; et al.
Abstract: This study aimed to evaluate the nutritional value of pasta enriched with legume or wheat gluten proteins and dried at varying temperature. A total of four isonitrogenous experimental diets were produced using gluten powder/wheat semolina (6/94, g/g) pasta and faba bean flour/wheat semolina (35/65, g/g) pasta dried at either 55°C (GLT and FLT, respectively) or 90°C (FVHT and GVHT, respectively). Experimental diets were fed to ten 1-month-old Wistar rats (body weight=176 (sem 15) g) for 21 d. Growth and nutritional, metabolic and inflammatory markers were measured and compared with an isonitrogenous casein diet (CD). The enrichment with faba bean increased the lysine, threonine and branched amino acids by 97, 23 and 10 %, respectively. Protein utilisation also increased by 75 % ( P <0·01) in FLT in comparison to GLT diet, without any effect on the corrected faecal digestibility ( P >0·05). Faba bean pasta diets' corrected protein digestibility and utilisation was only 3·5 and 9 %, respectively, lower than the CD. Growth rate, blood composition and muscle weights were not generally different with faba bean pasta diets compared with CD. Corrected protein digestibility was 3 % lower in GVHT than GLT, which may be associated with greater carboxymethyllysine. This study in growing rats clearly indicates improvement in growth performance of rats fed legume-enriched pasta diet compared with rats fed gluten–wheat pasta diet, regardless of pasta drying temperature. This means faba bean flour can be used to improve the protein quality and quantity of pasta.